FORMULASI DAN UJI MUTU FISIK SEDIAAN KRIM ANTI JERAWAT DARI EKSTRAK DAUN PEPAYA (Carica papaya L.) - Zukhri, Saifudin; Andasari , Sholikhah Deti; Muchson , Muchson (Universitas Muhammadiyah Klaten, 2018)
Extract leaves pepaya compound containing karpain alkaloid can bring to a bitter taste and having activity of obstruent against bacteria propionibacterium acnes that causes for acne.This report aims to understand extract leaves papaya can be made in the preparation anti acne cream, and influence distinction concentration extract leaves pepaya of physical preparations quality and cream having influence optimal with low extract leaves pepaya % 1, 2 %, 3 %. Extract of papaya leaves made by maceration for 5 days using solvent ethanol 96 %. Extract of papaya leaves made cream with M/ A type. Cream extract leaves papaya made with low different, the 1st formula with low extract 1%, 2nd formulas with low extract 2%, 3rd formula with low extract 3% and 4th formula without concentration extract. Cream and physical tested quality, quality testing covering the physical: organoleptic, the homogenity, the southwestern spread, the southwestern attaching, the pH, and the southwestern protection. Data analyzed normality with kolmogrov-smirnov followed by test homogeneity with homogency of variances and analyzed by statistic one-way anova if there is a difference followed by tukey HSD. The result showed that leaves papaya with concentration 1% , 2% , 3% can be made of preparations cream affecting physical cream quality preparations .Cream extract leaves papaya on formula II (concentration extract 2 %) has its attaching of 1.65±0.23 seconds , the spread 6.40±0.17 cm is the result of higher than the to a formula I (concentration extract 1 %) power attaching of 1.08±0.05 seconds, the spread of 6.26±0.30 cm and formula iii (concentration extract 3%) has its attaching 1.25 ± 1.11 seconds, the spread 7.03±0.32 cm.